Weevil resistant sweetpotato through biotechnology - International Potato Center (2011)
With the aim of “feeding the people, not the weevils” this project is combining conventional breeding and biotechnology to combat the pernicious and devastating consequences of sweetpotato weevil. Results to date include the identification of three insecticidal proteins and the introduction of putative resistance genes into sweetpotato varieties. The resistance levels will be measured in the following months, with continuation to field trials if those levels are significant.